Hepatic processing of mercuric ions facilitates delivery to renal proximal tubules. (15th April 2022) - Barfuss, Delon W.; Buchanan, John T.; Joshee, Lucy; Pittman, Elizabeth H.; D'Souza, Nigel; Matta, Kayla E.; Brownlee, Ryan T.; Bridges, Christy C.
Highlights: Hepatic processing of mercury is required for urinary excretion. Mercuric ions appear to become bound to glutathione within the liver. Mercury-glutathione complexes are transported by multidrug resistance proteins 3 and 5. Abstract: Mercury (Hg) is a toxic heavy metal to which humans are exposed on a regular basis. Hg has a high affinity for thiol-containing biomolecules with the majority of Hg in blood being bound to albumin. The current study tested the hypothesis that circulating Hg-albumin complexes are taken up into hepatocytes and processed to form Hg-glutathione (GSH) conjugates (GSH-Hg-GSH). Subsequently, GSH-Hg-GSH conjugates are exported from hepatocytes into blood via multidrug resistance transporters (MRP) 3 and 5. To test this hypothesis, the portal vein and hepatic artery in Wistar rats were ligated to prevent delivery of Hg to the liver. Ligated and control rats were injected with HgCl2 or GSH-Hg-GSH (containing radioactive Hg) and the disposition of Hg was assessed in various organs. Renal accumulation of Hg was reduced significantly in ligated rats exposed to HgCl2 . In contrast, when rats were exposed to GSH-Hg-GSH, the renal accumulation of Hg was similar in control and ligated rats. Experiments using HepG2 cells indicate that Hg-albumin conjugates are taken up by hepatocytes and additional experiments using inside-out membrane vesicles showed that MRP3 and MRP5 mediate the export of GSH-Hg-GSH from hepatocytes. These data are the first to show that Hg-albumin complexes are processed within hepatocytes to form GSH-Hg-GSH, which is, in part, exported back into blood via MRP3 and MRP5 for eventual excretion in urine.